2013
DOI: 10.1103/physrevb.87.054111
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transitions and electronic phenomena at 180-degree domain walls in rhombohedral BaTiO3

Abstract: The structure and electronic phenomena at the 180-degree domain wall in the rhombohedral phase of BaTiO 3 are described using Landau-Ginzburg-Devonshire theory. Dependent on the wall orientation, two types of domain wall behaviors are identified. The low-energy "achiral" phase occurs in the vicinity of the {110} orientation and has odd polarization profile invariant with respect to inversion about the wall center. The "chiral" phase occurs around {211} wall orientations and corresponds to mixed parity domain w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 55 publications
0
42
1
Order By: Relevance
“…This is illustrated in figure 7(b), where the normalized variation of the free-carrier concentration is plotted as a function of the tilt angle θ (after [85], for the material parameters of PbZr 0.2 Ti 0.8 O 3 ). Eliseev et al [90] have shown that the internal structure of ferroelectric DWs may be strongly correlated with current atomic force microscope (AFM) contrast, suggesting the use of current AFM for detecting phase transitions in DW structure.…”
Section: Conduction Of Domain Wallsmentioning
confidence: 99%
“…This is illustrated in figure 7(b), where the normalized variation of the free-carrier concentration is plotted as a function of the tilt angle θ (after [85], for the material parameters of PbZr 0.2 Ti 0.8 O 3 ). Eliseev et al [90] have shown that the internal structure of ferroelectric DWs may be strongly correlated with current atomic force microscope (AFM) contrast, suggesting the use of current AFM for detecting phase transitions in DW structure.…”
Section: Conduction Of Domain Wallsmentioning
confidence: 99%
“…This is particularly disappointing since the 180° domain walls have been predicted to exhibit the largest band gap reduction and magnetization out of the three possible domain wall variants in BiFeO3. 12,20 Moreover, the structure and properties of 180° ferroelectric domain walls have been extensively studied theoretically in recent years; 20,21 and a non-Ising character of the 180° domain wall, arising from flexoelectric effects, has been proposed. 22 Therefore, experimental verification of the existence of periodic 180° stripe domains in BiFeO3 is important for better understanding the domain formation mechanism, domain wall structure, and its contributions to magnetic and electric properties in this multiferroic material.…”
mentioning
confidence: 99%
“…[5][6][7][8] The results from Ref. 8 suggest that the approximation neglecting flexoelectricity, which is used in the present paper, provides an acceptable accuracy for the description of the structure of the walls.…”
Section: Rhombohedral Phasementioning
confidence: 58%
“…Equations (11) possess a certain symmetry. One can note that if the polarization profile {P 1 (z),P 2 (z)} satisfies the system (11), then {P 1 (z), − P 2 (z)} will also be a solution, and these two solutions are energetically equivalent, because (8) does not contain odd powers of P 2 . This implies that the Bloch walls are bistable.…”
Section: A Approximation Neglecting Electromechanical Couplingmentioning
confidence: 99%
See 1 more Smart Citation